PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN, PROFITABILITAS DAN FINANCIAL DISTRESS TERHADAP NILAI PERUSAHAAN - Saputra, Aldo; Lukman, Iing; Indriani, Wiewiek (Universitas Malahayati, 2021)
This study aims to determine how the effect of liquidity, firm size, profitability and financial distress on firm value. The type of data used in this study is secondary data obtained from the official website of the Annual Report. The population in this study are cigarette companies listed on the Indonesia Stock Exchange. Sampling using purposive sampling technique using certain criteria. Data analysis in this study used several methods, including multiple linear regression analysis, namely simultaneous test and partial test. The results of this study indicate that company size has no effect on firm value, while liquidity, profitability and financial distress have an effect on firm value. Research on cigarette companies listed on the IDX for the period 2017–2019. Research on the activities of cigarette companies listed on the IDX during the period 2017 to 2019 is based on the closing of the Indonesia Stock Exchange. The value of the company in this study through liquidity, company size, profitability and financial distress in the period 2017 – 2019.Keywords: liquidity, firm size, profitability, financial distress, and firm value